2015
DOI: 10.1175/jcli-d-14-00117.1
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of the Southern Ocean in Anthropogenic Carbon and Heat Uptake in CMIP5 Models

Abstract: The authors assess the uptake, transport, and storage of oceanic anthropogenic carbon and heat over the period 1861–2005 in a new set of coupled carbon–climate Earth system models conducted for the fifth phase of the Coupled Model Intercomparison Project (CMIP5), with a particular focus on the Southern Ocean. Simulations show that the Southern Ocean south of 30°S, occupying 30% of global surface ocean area, accounts for 43% ± 3% (42 ± 5 Pg C) of anthropogenic CO2 and 75% ± 22% (23 ± 9 × 1022 J) of heat uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
482
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 540 publications
(512 citation statements)
references
References 95 publications
27
482
0
3
Order By: Relevance
“…Meanwhile, less than half of the heat stored on the equatorward flank of the ACC (40-50 • S) is derived from local surface heat uptake; the rest is due to convergence of heat by the ocean. These patterns are broadly consistent with previous modeling studies 26,27 and the observations ( Fig. 1).…”
supporting
confidence: 93%
“…Meanwhile, less than half of the heat stored on the equatorward flank of the ACC (40-50 • S) is derived from local surface heat uptake; the rest is due to convergence of heat by the ocean. These patterns are broadly consistent with previous modeling studies 26,27 and the observations ( Fig. 1).…”
supporting
confidence: 93%
“…Here, regions critical for biological production and carbon uptake are associated with mode and intermediate water formation locations (Sarmiento et al, 2004;Sallée et al, 2012). Despite the fact that the simulated net uptake rates of atmospheric CO 2 in the SO are mostly overestimated compared to the values derived from observations (as shown in this study), Frölicher et al (2015) show that the CMIP5 models underestimate the anthropogenic-carbon storage in the Southern Ocean. This indicates either a shortcoming in the simulated large-scale overturning circulation or too strong a sink of non-anthropogenic carbon simulated here.…”
Section: Discussionmentioning
confidence: 44%
“…A large spread across all models was found (nearly 6 fold) and the spatial distribution of soil carbon, especially in the northern latitudes was found to be poor in comparison to HWSD and NCSCD, which means that most ESMs were poorly representing grid-scale soil carbon. Frölicher et al (2015) showed that CMIP5 models appeared to capture the observed pattern of anthropogenic carbon storage in the ocean, particularly in the Southern Ocean. However, overall they underestimate the magnitude of the observed oceanic global anthropogenic carbon storage since the pre-industrial.…”
Section: T Ziehn Et Al: Access-esm1 Historical Simulationsmentioning
confidence: 99%